2017
DOI: 10.1093/gji/ggx500
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inversion of refraction seismic traveltime data

Abstract: S U M M A R YWe apply a Bayesian Markov chain Monte Carlo (McMC) formalism to the inversion of refraction seismic, traveltime data sets to derive 2-D velocity models below linear arrays (i.e. profiles) of sources and seismic receivers. Typical refraction data sets, especially when using the far-offset observations, are known as having experimental geometries which are very poor, highly ill-posed and far from being ideal. As a consequence, the structural resolution quickly degrades with depth. Conventional inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Considering that hypocenter locations and velocity model are inherently linked to each other (coupled hypocenter-velocity problem, e.g., Kissling, 1988;Thurber, 1992;Kissling et al, 1994) especially in the local earthquake case, it is indicated to simultaneously invert for hypocenters and velocity structure (and/or station corrections). In this study, we use a Bayesian approach (Bayes, 1763), which has been applied in a number of geophysical studies (Tarantola et al, 1982;Duijndam, 1988a,b;Mosegaard and Tarantola, 1995;Gallagher et al, 2009;Bodin et al, 2012a,b;Ryberg and Haberland, 2018). This approach 8 https://doi.org/10.5194/se-2020-192 Preprint.…”
Section: Probabilistic Bayesian Inversionmentioning
confidence: 99%
“…Considering that hypocenter locations and velocity model are inherently linked to each other (coupled hypocenter-velocity problem, e.g., Kissling, 1988;Thurber, 1992;Kissling et al, 1994) especially in the local earthquake case, it is indicated to simultaneously invert for hypocenters and velocity structure (and/or station corrections). In this study, we use a Bayesian approach (Bayes, 1763), which has been applied in a number of geophysical studies (Tarantola et al, 1982;Duijndam, 1988a,b;Mosegaard and Tarantola, 1995;Gallagher et al, 2009;Bodin et al, 2012a,b;Ryberg and Haberland, 2018). This approach 8 https://doi.org/10.5194/se-2020-192 Preprint.…”
Section: Probabilistic Bayesian Inversionmentioning
confidence: 99%
“…This leads to characteristic shifts when calculating conventional average values to determine a reference (mean) model. However, to be able to derive a reference model, Ryberg & Haberland (2018) suggested a modified averaging procedure (in the following we use the term modified averages). Essentially, only velocity value samples with a probability exceeding the prior distribution are taken into account to calculate averages and standard deviations.…”
Section: A P P L I C At I O N T O S Y N T H E T I C Datamentioning
confidence: 99%
“…Essentially, only velocity value samples with a probability exceeding the prior distribution are taken into account to calculate averages and standard deviations. Details can be found in Ryberg & Haberland (2018).…”
Section: A P P L I C At I O N T O S Y N T H E T I C Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Rumpf and Tronicke () used a particle swarm optimizer to solve the tomographic problem and quantify uncertainties using a one‐dimensional layer‐based model parameterization. More recently, Ryberg and Haberland () directly applied a Bayesian MCMC formalism to invert refraction data and parameterized the velocity model using Voronoi tesselation and triangulated meshes. To our knowledge, no study has been published on the application of EA to the seismic tomography problem for a large number of model parameters.…”
Section: Introductionmentioning
confidence: 99%